Reading workplace dynamics : a post-pandemic professional ethos in public libraries - Irvin, Vanessa; Mehra, Bharat (Advances in librarianship ;, 2024)
During the 2020-2023 years of the pandemic, when it came to the workplace, public librarians creatively adjusted their practices and their praxis to keep communities engaged with a myriad of virtual information services and distal information delivery during lockdown, lasting for often long and uncertain timeframes. Library staff then had to transition back to providing information services that resembled pre-pandemic services, but with added virtual options that library users had become accustomed to. How the pandemic affected librarian praxis has become a testimony of how librarian ethos has grown and become stronger for the lessons learned. Defining the librarian ethos as the character of the librarian identity, Reading Workplace Dynamics offers a renewed ethos for public librarianship synthesizing frontline practitioner outcomes with scholarship via a blend of chapters presenting innovative and bold testimony on ways in which COVID-19 forever changed public librarianship. With a diverse geocultural scope, all chapters mindfully focus on the value of regionality and geoculture, centering and highlighting new voices to document the knowledge and wisdom of scholars and practitioners with front-line experience and longevity in public library services. Reading Workplace Dynamics appeals to public library professionals globally interested and invested in their professional development, and wider readers seeking to understand experiences, practices, and initiatives in public libraries.